Questions Frequently Asked by Marine Mammal Density Surface Modelers - Jason J. Roberts; Dave Miller; Elizabeth Becker; Phil Bouchet; Megan Ferguson; Tina Yack, Ph.D.; Pat Halpin; Len Thomas (Open Science Framework, 2022)
A collection of methodology questions, with answers, frequently asked by density surface modelers during marine mammal modeling projects